REGISTER LANGUAGE IN THE VICTORIAN ERA AS REFLECTED IN THE CHARLES DICKENS "OLIVER TWIST" - Dina Maulida Purbasari; Syahfitri Purnama (INFERENCE: Journal of English Language Teaching, 2022)
The aim of this research is to know about Language Register that being used in the Victorian Era. 1) How Industrial Revolution effects on the language choices in a Victorian Era, 2) What the expressions of Register Language are used in the Victorian Era, and 3) How Language Register cannot be separated from the use of language styles. The design of this research is a qualitative descriptive study with content analysis to find out about the context, purposes, and content messages of utterances in the communication. Analyzing and making inferences about the utterances producers as the addressors and the audience as the addressee of the text. It has found problems in society during Victorian era, especially to harsh conditions of orphans and children during the Industrial revolution which is the main focus. 1) Realism projected in realistic characters and setting, comprehensive detail about everyday occurrences, plausible plot, dialects of community, character development, and the importance in depicting social class. These elements are the background for choosing words, choosing language in all utterances between speakers, each character. Representing the use of language in the Victorian Era. 2). Many register languages are used, there are types of Register variation expressions used, the choice of lexical in a conversation sentence that refers to the context of the situation, the context of addressee and addressors, also the typical language variation used in the Victorian era. In the context of the situation, the register also influenced of choosing the right sequence of sentences intended by the interlocutor, in a particular situation. 3). There are variety of language in utterances where style is widely used. Utterances in daily context of living in the Victorian Era occurring in every conversation between speakers. This research is expected to be useful in obtaining information about Register Language and the advantages for English second Language learner and Learning English for special purposes. Broaden vocabulary and sentences of a Register Language can affect the ability of communication skill especially speaking skill.